2016
DOI: 10.1515/hmbci-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

A link between hypothyroidism, obesity and male reproduction

Abstract: Hypothyroidism is a condition in which the serum levels of thyroid hormones are below that necessary to carry out physiological functions in the body. Hypothyroidism is related to obesity as an increase in body weight gain is seen in hypothyroid patients. Moreover, an inverse correlation between free thyroxine values and body mass index has been reported. Leptin, a polypeptide hormone produced by adipocytes, was originally thought to be an antiobesity hormone due its anorexic effects on hypothalamic appetite r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 101 publications
1
17
0
2
Order By: Relevance
“…This is not only associated with a variety of chronic diseases, such as hyperlipidemia, diabetes mellitus, hypertension, but has also been demonstrated to have hazardous effects on the reproductive system and fertility [2][3][4][5]. Moreover, obesity can affect male infertility by affecting spermatogenesis, thus reducing fertilization rate [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This is not only associated with a variety of chronic diseases, such as hyperlipidemia, diabetes mellitus, hypertension, but has also been demonstrated to have hazardous effects on the reproductive system and fertility [2][3][4][5]. Moreover, obesity can affect male infertility by affecting spermatogenesis, thus reducing fertilization rate [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One study 23 reported that thyroid disease negatively affects spermatogenesis and consequently may cause male infertility. Decreased libido or impotence is also present in hypothyroidism 24 .…”
Section: Introductionmentioning
confidence: 99%
“…is alteration in thyroid hormone (TH) levels. 4 TH has long been established as a factor affecting testicular development with associated reproductive functions, particularly during the prepubertal period. 4 These effects are manifested by the effect of TH on Leydig, Sertoli and germ cells disturbing erectile functions and sperm parameters (count, morphology and motility; both progressive and non-progressive).…”
mentioning
confidence: 99%
“…4 TH has long been established as a factor affecting testicular development with associated reproductive functions, particularly during the prepubertal period. 4 These effects are manifested by the effect of TH on Leydig, Sertoli and germ cells disturbing erectile functions and sperm parameters (count, morphology and motility; both progressive and non-progressive). 5,6 Hypothyroidism in particular increases the sperm transit time through the epididymis, which causes a reduction in total and daily sperm productions.…”
mentioning
confidence: 99%
See 1 more Smart Citation